Autophagy and nutrigenomics: a winning team against chronic disease and tumors - Chiarelli, Roberto; Caradonna, Fabio; Naselli, Flores (Frontiers in Nutrition, 2024)
Autophagy, a vital cell process, has garnered attention for its role in various diseases and potential therapeutic interventions. Dysregulation of autophagy contributes to conditions such as metabolic diseases, neurodegenerative disorders, and cancer. In diseases such as diabetes, autophagy plays a crucial role in islet β-cell maintenance and glucose homeostasis, offering potential targets for therapeutic intervention. Nutrigenomics, which explores how dietary components interact with the genome, has emerged as a promising avenue for disease management. It sheds light on how diet influences gene expression and cellular processes, offering personalized approaches to disease prevention and management. Studies have showed the impact of specific dietary components, such as polyphenols and omega-3 fatty acids, on autophagy processes, suggesting their potential therapeutic benefits in neurodegenerative conditions and metabolic disorders. In cancer, autophagy's dual role in either suppressing tumorigenesis or promoting cancer cell survival underscores the importance of understanding its modulation through dietary interventions. Combined with conventional chemotherapy drugs, dietary compounds show synergistic effects in cancer treatment. Furthermore, phytochemicals such as Indicaxanthin have been found to epigenetically regulate genes involved in autophagy, offering novel insights into personalized cancer therapies.This comprehensive review has the aim to study the autophagy in a combined view with nutrigenomics properties effects of some dietary molecules in maintaining cellular homeostasis and responding to pathological stimuli.Overall, the intersection of autophagy and nutrigenomics effect of bioactive compounds holds promise for developing targeted interventions for various diseases, emphasizing the significance of dietary interventions in disease prevention and management.